PHYTOCHEMICAL CHARACTERIZATION AND NUTRITIONAL EVALUATION OF Ficus septica FOR AQUAFEED DEVELOPMENT IN HERBIVOROUS FISH: KARAKTERISASI FITOKIMIA DAN EVALUASI NUTRISI Ficus septica UNTUK PENGEMBANGAN PAKAN AKUATIK PADA IKAN HERBIVORA - Islamy, R. Adharyan; Setyowati, Najwa Lutfi; Ni'matullah, Syakir (Program Studi Akuakultur, Universitas Bangka Belitung, 2025)
The sustainability of aquaculture relies heavily on the development of nutritionally balanced and cost-effective feed alternatives that reduce dependency on conventional protein sources. F. septica, a medicinal plant rich in bioactive compounds, offers potential as a novel functional feed ingredient for herbivorous fish. This study aimed to characterize the phytochemical profile and evaluate the proximate nutritional composition of F. septica leaves, and to assess their effects on growth performance and feed utilization in herbivorous fish. Phytochemical screening revealed high levels of phenolics (33.5 ± 2.1 mg/g), flavonoids (28.7 ± 1.3 mg/g), and tannins (16.1 ± 0.9 mg/g), indicating strong antioxidant and antimicrobial potential. Proximate analysis showed that F. septica leaves contained 18.7% protein, 40.7% nitrogen-free extract, and 16.3% fiber. Feeding trials with diets containing 0% (control), 5%, and 10% F. septica leaf powder demonstrated significant improvements in weight gain, specific growth rate, and feed conversion ratio in the 5% and 10% groups (p < 0.05), without compromising survival. These results suggest that F. septica can be effectively utilized as a nutrient-rich, bioactive aquafeed additive for herbivorous fish. Further research on digestibility, long-term effects, and residue safety is recommended to validate its practical applications in commercial aquaculture.